"Banal Apocalypse": An Interview with Author Ta-wei Chi on the New Translation of The Membranes. Issue 2 (1st December 2020) - Park, Jane Chi Hyun; Chi, Ta-wei
Abstract: This interview is based on a series of email exchanges in November 2019 between Taiwanese writer and scholar Ta-wei Chi and Korean American scholar Jane Chi Hyun Park about Chi's queer speculative novella, The Membranes . The first section provides a summary of the novella, which was recently translated into English by Ari Heinrich. The second section paints a picture in broad brush strokes of the contexts in which Chi wrote The Membranes —taking into consideration key cross-cultural influences and critical reception in Taiwan in the 1990s. It also examines the cultural and political relevance of Chi's creative predictions about the future within the present historical moment. Finally, it explores afterlives for the novella in the form of sequels and possible cinematic adaptations.